ERROR ANALYSIS OF CONJUNCTIVE ADVERB USED BY THE EIGHTH GRADE STUDENTS - Ikhratulsandi Ikhratulsandi; Rofiqoh Rofiqoh; Muhammad Arid (Tadulako University, 2021)
This research was aimed at finding out the errors on conjunctive adverb found in descriptive text written by the eighth grade students of SMP Negeri 1 Sindue. The researcher analyzed the data by applying simple descriptive analysi. The research sample was 22 students. The instruments of data collection were a writing test. The students were assigned to write descriptive text by using conjunctive adverbs. The result of data analysis showed that there were two errors made by students, i.e. misplace of conjunctive adverbs and inappropriate conjunctive adverbs. There were 7 or 38.88% errors in misplace of conjunctive adverbs, 3 or 16.66% errors inappropriate conjunctive adverbs, and 18 or 94.73% used conjunctive adverbs correctly. The occurrence of these errors may be caused by misunderstanding of the teacher’s explanation in the target language and may be also caused by the inability of using rules into context eventhough they have been taught items in the target language repeatedly. The causes of these errors included in the category of intra-lingual errors i.e. the false concept hypothesis and incomplete application of the rules.